PENERAPAN ARSITEKTUR PERILAKU PADA PERANCANGAN PUSAT PELATIHAN OLAHRAGA DISABILITAS FISIK DI GORONTALO - Muh. Fadrianto Tomu; Satar Saman; Lydia Tatura (Universitas Negeri Gorontalo, 2023)
ABSTRACT Gorontalo Province is one of the regions in Indonesia with a rapidly growing population of people with disabilities, reaching 6,945 individuals spread across 6 districts/cities. Based on this number, Gorontalo is one of the areas that frequently participates in the PEPARNAS (National Paralympic Week) event, which is held every 4 years. However, Gorontalo lacks the facilities to accommodate the training of physically disabled athletes and support their spirit for continuous development. The aim of the Physical Disability Sports Training Center Design is to provide a sports training facility for individuals with physical disabilities in Gorontalo, equipped with disability-friendly infrastructure and facilities. The methods employed in this design included data collection, site analysis, benchmarking, and literature studies. The physical disability sports training center in Gorontalo was designed based on the needs of individuals with physical disabilities as the main actors, using a behavioral architecture approach. Behavioral architecture is an approach in the field of architecture that emphasizes the connection between a space or building and its users and environment through the transformation of form and appearance of the building, site mass processing, and physical completeness of the designed building, taking into account the materials used in the design to provide safety and comfort for users during activities inside the facility. The research result was a building model of the Physical Disability Sports Training Center in Gorontalo as a facility to accommodate sports training for physically disabled athletes, equipped with disability-friendly infrastructure and facilities, creating comfort and safety during activities within the space or building, as well as during the training, development, and nurturing process in the field of sports. ABSTRAKProvinsi Gorontalo merupakan salah satu daerah di Indonesia dengan populasi penyandang disabilitas yang pesat yaitu mencapai 6.945 jiwa yang tersebar di 6 Kabupaten/Kota. Bedasarkan jumlah tersebut, Gorontalo menjadi salah satu daerah yang sering mengikuti ajang PEPARNAS (Pekan Paralimpiade Nasional) yang diselenggarakan 4 tahun sekali. Akan tetapi di Gorontalo sendiri belum memiliki fasilitas yang dapat mewadahi latihan para atlet disabilitas fisik untuk penunjang semangat para atlet agar terus berkembang. Tujuan dari Perancangan Pusat Pelatihan Olahraga Disabilitas Fisik ialah untuk mewujudkan sebuah fasilitas pelatihan olahraga bagi penyandang disabilitas fisik di Gorontalo dengan sarana dan prasarana yang ramah terhadap disabilitas. Metode yang digunakan dalam perancangan ini ialah metode pengumpulan data, analisis site, studi banding dan studi literatur. Pusat pelatihan olahraga disabilitas fisik di Gorontalo akan dirancang berdasarkan kebutuhan disabilitas fisik sebagai pelaku utama dengan pendekatan tema arsitektur perilaku. Arsitektur Perilaku adalah sebuah pendekatan dalam ilmu arsitektur yang sangat menekankan keterkaitan antara sebuah ruang atau bangunan dengan pengguna dan lingkungannya melalui transformasi bentuk dan penampilan bangunan, pengolahan tata massa tapak, serta kelengkapan fisik bangunan yang didesain sedemikian rupa dengan memperhatikan material yang digunakan dalam perancangan agar dapat memberikan keamanan dan kenyamanan kepada pengguna saat beraktivitas didalamnya. Hasil dari penelitian ini berupa model bangunan Pusat Pelatihan Olahraga Disabilitas Fisik di Gorontalo sebagai fasilitas untuk mewadahi pelatihan olahraga bagi para atlet disabilitas fisik dengan sarana dan prasarana yang ramah terhadap disabilitas sehingga dapat tercipta kenyamanan dan keamanan saat beraktifitas dalam ruang atau bangunan, serta dalam proses pelatihan, pembinaan dan pengembangan pada bidang olahraga